The Completion of AL-Nabigha AL-Ja'adi's Poetry Collect, study and investigation - , Prof. Dr. Ali Mohsen Badi (Thi Qar Arts Journal, 2021)
Redressing the recent efforts concerned with collecting Al-Nabigha Al-Jaadi's poetry collection is the subject of this study. The Diwan has an ancient origin, which was collected and taken care of by the efforts of a group of Arabic scholars and its early narrators, but it is still missing. The orientalists were prior to sensing this defect, so some of them interested in ancient Arabic literature tried to collect what was scattered from the poetry of Al-Nabigha Al-Jaadi in the ancient sources in all its directions, so in the middle of the twentieth century the scientific community witnessed its first collection. Then other efforts continued to care for the poetry of Al-Nabigha Al-Jaadi and went in two directions, the first: republishing the first European collection with new additions, and this direction was represented by two Arabic publications of the Diwan. And the other direction: to catch up with new texts on the first of the two Arabic bulletins, and this trend was represented by two rectifications, each of which was included in a university thesis concerning the literature of Al-Nabigha Al-Ja'adi.